Supramolecular packing of alkyl substituted Janus face all-cis 2, 3, 4, 5, 6-pentafluorocyclohexyl motifs. Issue 28 (23rd June 2021) - Clark, Joshua L.; Taylor, Alaric; Geddis, Ailsa; Neyyappadath, Rifahath M.; Piscelli, Bruno A.; Yu, Cihang; Cordes, David B.; Slawin, Alexandra M. Z.; Cormanich, Rodrigo A.; Guldin, Stefan; O'Hagan, David
Abstract : Theory and Langmuir isotherm analysis was used to explore the conformations and molecular packing of alkyl all- cis 2, 3, 4, 5, 6-pentafluorocyclohexyl motifs, which are prepared by direct aryl hydrogenations from alkyl- or vinyl-pentafluoroaryl benzenes. Abstract : This study uses X-ray crystallography, theory and Langmuir isotherm analysis to explore the conformations and molecular packing of alkyl all- cis 2, 3, 4, 5, 6-pentafluorocyclohexyl motifs, which are prepared by direct aryl hydrogenations from alkyl- or vinyl-pentafluoroaryl benzenes. Favoured conformations retain the more polar triaxial C–F bond arrangement of the all- cis 2, 3, 4, 5, 6-pentafluorocyclohexyl ring systems with the alkyl substituent adopting an equatorial orientation, and accommodating strong supramolecular interactions between rings. Langmuir isotherm analysis on a water subphase of a long chain fatty acid and alcohol carrying terminal all- cis 2, 3, 4, 5, 6-pentafluorocyclohexyl rings do not show any indication of monolayer assembly relative to their cyclohexane analogues, instead the molecules appear to aggregate and form higher molecular assemblies prior to compression. The study indicates the power and potential of this ring system as a motif for ordering supramolecular assembly.